ANALISA VEGETASI HUTAN PEGUNUNGAN DI TAMAN NASIONAL GUNUNG CIREMAI, MAJALENGKA, JAWA BARAT - Purwaningsih, Purwaningsih; Yusuf, Razali (Perhimpunan Biologi Indonesia, 2008)
ABSTRACTThe Mountain Rain Forest Vegetation Analysis in Ciremai Mountain NationalPark, Majalengka, West Jawa. Vegetation study on some different altitude in CiremaiMountain National Park has been carried out with a quadrat methode. Ten plots were setup in altitude at 1600? 2050 m. The results of a floristic inventory of 1.2 hectare sampledplot show that there were 57 species of 42 genera in 28 families, represented by 1069individuals. The two leading families in terms of number of species were Euphorbiaceaeand Fagaceae while according to the most prominent species were Engelhardia spicata(Juglandaceae). There are differences of both zonation and altitudinal forest disturbance.The zone of 1600?1700 m asl. dominated by secondary species such as Saurauia nudiflora,Glochidion arborescens, Glochidion rubrum, Ficus fistulosa, Vernonia arborea andVillebrunea rubescens. In altitude of >1900 m asl. dominated by primary species such asMacropanax dispermum, Astronia spectabilis, Turpinia spaerocarpa, Elaeocarpus oxypyrenand Syzygium laxiflorum. The forest structure could be seen by diameter and heightstem classes distribution. Although the most of trees are small in size, but there havebeen still some largest trees were Engelhardia spicata, Turpinia sphaerocarpa and Astroniaspectabilis.Key words: West Java, Ciremai Mountain National Park, forest zonation, structure and speciescomposition